PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN (STUDI PADA PT. BAHANA BUANABOX, SAYUNG) - Ariyanto, Ariyanto; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2017)
Many new packaging industries have emerged in Indonesia resulted in the competitive of packaging industry in Indonesia will be more stringent, so that PT. Bahana BuanaBox, Sayung should improve the quality and performance of employees in producing the results their products because consumers are increasingly selective in choosing and using a product that will have to be consumed. This study aimed to analyze the influence of education and training, participation, and empowerment of the performance of employees of PT. Bahana BuanaBox, Sayung.The population used in this study were all employees of PT. Bahana BuanaBox, Sayung. The sampling technique used was purposive sampling. Criteria samples taken were all employees of the production of PT. Bahana BuanaBox, Sayung who has worked for more than three years totaling 200 employees. Methods of data collection in this study using questionnaires and interviews. Methods of data analysis using multiple regression.Based on the results of research, education and training, participation, and empowerment positive influence on employee performance, based on the results of goodness of fit, it can be said that the model can be used to predict the performance of employees while the test results from the coefficient of determination, employee performance is able to be explained by education and training, participation, and empowerment of 73.8%.